The Post Governance: Paving the Way for Teenagers’ Role in Society Through Social Media - Sukaso, Sukarso; Dasuki, Niken Paramarti; Noviko, Sendy (Technium Social Sciences Journal, 2024)
When there is an emphasis on governance practices or governance in Indonesia, including villages is also a priority. Therefore, it is interesting to study how governance is in the era of use and utilization of social media in village communities. By using a case study approach through interviews and focus group discussions, it turns out that this study produces a new pattern or model of governance practice. The findings of the governance model in this social media era are post governance, it turns out that the group of teenagers who dominantly use social media have the potential to become the fourth actor with a volunteer-altruist spirit for the welfare of society. This result, or post-gavernance, has two options, namely the tetragonal model and the pyramid model. The results of this study can be generalized to explain the same phenomenon in other villages or at local, regional and national levels.